Branding Tempat dan Produksi Ruang (Studi Kasus: Kawasan Cibadak, Kota Bandung) - Medina Savira; Fikri Zul Fahmi (TATALOKA, 2020)
Local governments frequently use place branding strategies to enhance regional competitiveness. One example is the Municipality of Bandung that attempted to brand Cibadak Area as Bandung’s Chinatown. The process of communication of the brand is the most important process in the effort to place branding. It is expected that the process can construct a brand image that is in accordance with the expectation of the government. It is argued that the process of communication the brand can be explained by the production of space, as the spatial production that occurs is able to construct a brand image that is accepted by society. This study aims to determine the space production process that has implications for brand image in Cibadak Area. This study uses qualitative method analysis. Based on this research, it is identified that there is a difference between the citizens perspective and the plan which is imagined by the government. This matter shows that there is a difference between brand image received by the community and brand identity desired by the government.